THE PURITY CONCEPT OF AL-FALIMBĀNI AND ITS CORRELATION WITH THE ISLAMIC MALAY SOCIETY: THE CONTENT ANALYSIS ON SAYR AL-SĀLIKĪN ILĀ IBĀDATI RABB AL-ĀLAMĪN’S SCRIPT - Muliadi, Muliadi; Ruslan, Ruslan; Maulana, Riyan; Widyanto, Anton (Islam Futura, 2022)
Al-Falimbān's thoughts in the ancient text of Sayr al-Sālikīn Ilā 'Ibādati Rabb al-Ālamn have influenced the dynamics of Malay Islamic society. One of the discussions in the text is the study of sanctification [ṭahārah]. This article examines the concept of al-Falimbānī ahārah in the Sayr al-Sālikīn text and its correlation with the observance of the Islamic Malay community in the 18th century. This journal has been carried out using a philological method with a content analysis approach. The results showed that the concept of the sanctity of Al-Falimbān, which is believed to be the standard of holiness that a Malay Muslim mukallaf should practice, is physical and spiritual purity. Physical purity is defined as removing all kinds of sensory and sensory impurity, while spiritual purity is defined as the ability to remove sensual and immaterial impurities.